Simulation Modeling in Sociology of Management: Methodology, Theory, Practice - Yu. D. Krasovsky (Управление)
The article outlines the main stages of the emergence, functioning and development of the process of simulation in the management sociology based on consulting activity, methods of designing simulation models in the specifics of business games. The author gradually reveals the little studied problems on specific descriptions of social technologies of gaming practice, «deciphering» the phenomenon of simulation modeling as a consulting and management resource. New in understanding this phenomenon is the author’s discovery of the teaching function of simulation modeling of management situations (visual graphics) in the improvement of teaching practice.